A Lyapunov-Razumikhin Condition of ISS for Switched Time-Delay Systems Under Average Dwell Time Commutation⁎This work was supported by the National Nature Science Foundation of China (No. 61873314), 111 project No. D17019 (China), the Government of Russian Federation (Grant 08-08), the Ministry of Science and Higher Education of Russian Federation, passport of goszadanie no. 2019-0898, and the Natural Science Foundation of Zhejiang Province, China (No. LY20F030008). Issue 2 (2020) - Zhang, Junfeng; Efimov, Denis
Abstract: A condition of ISS is proposed for nonlinear time-delay systems based on the Lyapunov-Razumikhin theory, which allows the rate of convergence to be evaluated. Then, this condition is used for ISS analysis of switched nonlinear time-delay systems with average dwell time switching. Finally, one example is given to verify the effectiveness of theoretical findings.